Trends in Nurse Practitioner and Physician Assistant Practice in Nursing Homes, 2000–2010. (13th November 2015) - Intrator, Orna; Miller, Edward Alan; Gadbois, Emily; Acquah, Joseph Kofi; Makineni, Rajesh; Tyler, Denise
Abstract : Objective: To examine nurse practitioner (NP) and physician assistant (PA) practice in nursing homes (NHs) during 2000–2010. Data Sources: Data were derived from the Online Survey Certification and Reporting system and Medicare Part B claims (20 percent sample). Methods: NP/PA state average employment, visit per bed year (VPBY), and providers per NH were examined. State fixed‐effect models examined the association between state regulations and NP/PA use. Principal Findings: NHs using any NPs/PAs increased from 20.4 to 35.0 percent during 2000–2010. Average NP/PA VPBY increased from 1.0/0.3 to 3.0/0.6 during 2000–2010. Average number of NPs/PAs per NH increased from 0.2/0.09 to 0.5/0.14 during 2000–2010. The impact of state scope‐of‐practice regulations was mixed. Conclusions: NP and PA scope‐of‐practice regulations impact their practice in NHs, not always as intended.